Prenatal Megacystis – Is Prediction of Outcome and Renal Function Possible? - Tschannen, Regina; Gobet, Rita; Wisser, Josef (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Objective To assess prenatal prognostic criteria for fetuses with megacystis in order to counsel parents.Methods In a retrospective observational study at a single tertiary referral center, we assessed the clinical course of 53 fetuses with megacystis cared for at the Department of Obstetrics of the University Hospital Zurich between 1995 and 2008 and followed them up for 2 to 12 years. We determined fetal karyotype, amniotic fluid volume and fetal urinary biochemistry as prenatal prognostic factors. The renal function of survivors was grouped according to age-related creatinine values. Using logistic regression analysis, gestational age-dependent discrimination curves and corresponding ROC curves for fetal urine, beta-2 microglobulin, osmolarity and chloride were calculated.Results 43 out of 53 fetuses underwent vesicocentesis, and spontaneous remission occurred in 3 fetuses. 15 fetuses survived, termination of pregnancy was requested in 23 cases, and 12 neonatal and 3 intrauterine deaths were observed. Reduced amniotic fluid volume showed a significant (p = 0.0027) increase of impaired renal function or perinatal death. Discrimination between survivors and non-survivors was complete for fetal urine beta-2 microglobulin with an area under the curve (AUC) of 1.0. For fetal urine osmolarity and fetal urinary chloride, the AUC was 0.81 and 0.76, respectively.Conclusion The assessment of prognosis for fetal megacystis should include fetal k aryotyping, determination of amniotic fluid and assessment of fetal urine biochemistry. Gestational age-dependent regression lines disclose clinically relevant discrimination and can be used as selection criteria for fetal interventions and parental counselling.
Keywords: fetus; megacystis; urine analysis; prognosis; age-dependent cut-off